An Examination of the Student's Proficiency in English Vocabulary and Translation Skills at the Third Semester Universitas Panca Sakti - Sari, Tiara Dian (CV. ULIL ALBAB CORP, 2024)
It is very important to learn English. Those who wish to learn a language must at least be proficient in translation. The purpose of this research is to determine the level of understanding and translation of students and the difficulties they face when studying English at Panca Sakti University so that the research finds solutions in solving the problems of each student's difficulties and English translation and vocabulary comprehension abilities in English. This research was conducted in the third semester of English teaching at Panca Sakti University. To collect information, the author used observation, interviews, skills tests, pre-tests and post-test for the ability to understand vocabulary, pre-tests and post-tests for the ability to understand word translation, and a literature review. The average score on the pre-test for students' ability to understand vocabulary is 69. 37, the average score for students' ability to translate is 65. 5, and the average post-test score for the ability to understand vocabulary is 80. 75, and the translation ability is 83. 25. According to research data. Both show that comprehension and translation abilities experienced a significant increase after a motivational approach was carried out and a little explanation about the importance of understanding vocabulary in translating English-Indonesian or Indonesian-English.